Toba na sae : Sejarah lembaga sosial politik abad xii-xx / Sitor Situmorang; Penyunting, Uswatul Chabibah dan Tri Agung S. - SITUMORANG, Sitor; USWATUL Chabibah; TRI Agung S. (Komunitas Bambu, 2009)
xx,548 hlm. : ilus. ; 21 cm.